Bobshannonite, Na2KBa(Mn, Na)8(Nb, Ti)4(Si2O7)4O4(OH)4(O, F)2, a new TS-block mineral from Mont Saint-Hilaire, Québec, Canada: Description and crystal structure. (2nd January 2018) - Sokolova, E.; Cámara, F.; Abdu, Y.A.; Hawthorne, F.C.; Horváth, L.; Pfenninger-Horváth, E.
Abstract: Bobshannonite, Na2 KBa(Mn, Na)8 (Nb, Ti)4 (Si2 O7 )4 O4 (OH)4 (O, F)2, is a new TS-block mineral from Mont Saint-Hilaire, Québec, Canada. It occurs as blocky crystals 0.5–1 mm across, perched on sérandite and albite. Other associated minerals are epididymite, catapleiite, aegirine, kupletskite, rhodochrosite and rhabdophane-(Ce). Bobshannonite occurs as vitreous to frosty, transparent to translucent very pale brown to orange brown crystals, has a very pale brown streak, hackly fracture and does not fluoresce under cathode or ultraviolet light. Cleavage is {001} very good, no parting was observed, Mohs hardness is ∼4, it is brittle and D calc. = 3.787 g/cm 3 . Crystals are twinned extensively and do not extinguish in cross-polarized light. Bobshannonite is triclinic, C 1, a = 10.839(6), b = 13.912(8), c = 20.98(1) Å, α = 89.99(1), β = 95.05(2), γ = 89.998(9)°, V = 3152(5) Å 3 . The six strongest reflections in the powder X-ray diffraction data [ d (Å), I, ( hkl )] are: 2.873, 100, (241, 241, 044, 044, 241, 241); 3.477, 60, (006); 3.193, 59, (224, 224); 2.648, 40, (402, 243, 243); 2.608, 35, (008, 226, 226); 1.776, 30, (249). Chemical analysis by electron microprobe gave Ta2 O5 0.52, Nb2 O5 19.69, TiO2 5.50, SiO2 26.31, Al2 O3 0.06, BaO 7.92, ZnO 1.02, FeO 0.89, MnO 26.34, MgO 0.06, Rb2 O 0.42, K2 O 2.38, Na2 O 4.05, F 0.70, H2 Ocalc. 1.96, O = –0.29, total 97.53 wt.%, where the H2 O content was calculated from the crystal-structure analysis. The empirical formula on the basis of 38 anions is Na1.89 (K0.93 Rb0.08 )Σ1.01 Ba0.95 (Mn6.85 Na0.52 Zn0.23 Fe0.23 2+ Mg0.03 Al0.02 )Σ7.88 (Nb2.73 Ti1.27 Ta0.04 )Σ4.04 (Si8.07 O28 )O9.32 H4.01 F0.68, Z = 4. The crystal structure was refined to R 1 = 2.55% on the basis of 7277 unique reflections [ F > 4σ( F )] and can be described as a combination of a TS (Titanium Silicate) block and an I (Intermediate) block. The TS block consists ofHOH sheets (H – heteropolyhedral, O – octahedral). The topology of the TS block is as in Group II of the Ti disilicates: Ti + Nb = 2 a.p.f.u. per (Si2 O7 )2 [as defined by Sokolova (2006)]. In the O sheet, ten [6] M O sitesare occupied mainly by Mn, less Na and minor Zn, Fe 2+, Mg and Al, with = 2.223 Å. In the H sheet, four [6] M H sites are occupied by Nb and Ti (Nb > Ti), with = 1.975 Å, and eight [4] Si sites are occupied by Si, with = 1.625 Å. The M H octahedra and Si2 O7 groups constitute the H sheet. The TS blocks link via common vertices of M H octahedra. In the I block, Ba and Kare ordered at the A P (1) and A P (2) sites with Ba:K = 1:1 and the two B P sites are occupied by Na. The ideal composition of the I block is Na2 KBa a.p.f.u. Bobshannonite, perraultite, surkhobite and jinshajiangite are topologically identical Group-II TS-block minerals. Bobshannonite is the Nb-analogue of perraultite. The mineral is named bobshannonite after Dr. Robert (Bob) D. Shannon (b. 1935), in recognition of his major contributions to the field of crystal chemistry in particular and mineralogy in general through his development of accurate and comprehensive ionic radii and his work on dielectric properties of minerals.